Идея классицизма у Л. В. Пумпянского (К постановке проблемы) [Lev Pumpyansky’s Idea of Classicism: A Very Brief Introduction] - Larocca, Giuseppina (Slavica Revalensia, 2014)
This introduction to Lev Pumpyansky’s (1891—1940) idea of Classicism focuses on the following problems: what is the meaning of the idea of Classicism in Pumpiansky’s terms? How did Pumpyansky apply this idea to the analysis of Russian poetry? What is the cultural background of Pumpyansky’s idea of Classicism? The article stresses the fact that Pumpyansky’s theory has several sources, e. g. the critical output of Vyacheslav Ivanov and Tadeusz Zieliński.